2014
DOI: 10.1177/0018726714530013
|View full text |Cite
|
Sign up to set email alerts
|

Explaining compliance: A multi-actor framework for understanding labour law compliance in China

Abstract: I argue that there is increasing evidence that multiple stakeholders, such as labour intermediaries and independent workers, are involved in the regulation of labour standards in China, resulting in increasing compliance with labour laws. In addition, I argue that the differential interests of multiple stakeholders lead to a variation in compliance across different labour law provisions. I find support for these arguments using original factory-level compliance data collected in southern China between 2009 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…Similarly, the waiving of the insistence for government permits does not imply that COSMOS accepts suppliers that are operating with inadequate safety standards because trusted third‐party certification must be presented instead. Unlike suppression, contextualization entails the sustainability managers’ active involvement in developing workable solutions for their suppliers, and this will decrease the likelihood of suppliers hiding actions and faking compliance (Chung, ; Jamali, Lund‐Thomsen, & Khara, ; Roberts, Engardio, Bernstein, Holmes, & Ji, ). Our data showed that sustainability managers were indeed committed to finding workable solutions for their suppliers and did not simply turn a blind eye when it became apparent that suppliers were struggling to comply with certain sustainability standards.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the waiving of the insistence for government permits does not imply that COSMOS accepts suppliers that are operating with inadequate safety standards because trusted third‐party certification must be presented instead. Unlike suppression, contextualization entails the sustainability managers’ active involvement in developing workable solutions for their suppliers, and this will decrease the likelihood of suppliers hiding actions and faking compliance (Chung, ; Jamali, Lund‐Thomsen, & Khara, ; Roberts, Engardio, Bernstein, Holmes, & Ji, ). Our data showed that sustainability managers were indeed committed to finding workable solutions for their suppliers and did not simply turn a blind eye when it became apparent that suppliers were struggling to comply with certain sustainability standards.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on COSMOS's supply chains in China as the main battleground for supplier sustainability management for most multinational companies in the consumer electronics industry (Chung, ; Roth, Tsay, Pullman, & Gray, ). COSMOS categorizes its suppliers based on their sustainability risk profile, which is related to the level of purchasing, the country of production, operational risks (such as use of hazardous chemicals in production processes), and the type of buyer–supplier relationship.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, China was of particular interest for a number of reasons. While China is currently the world's manufacturing center, most Chinese factories are struggling with the implementation of labor and environmental standards imposed by WBFs (e.g., Chung, 2015). The WBF assured us that the majority of its risky suppliers are located in China, a fact which also pointed to high levels of potential barriers.…”
Section: Methodsmentioning
confidence: 99%
“…While China is currently the world's manufacturing center, most Chinese factories are struggling with the implementation of labor and environmental standards imposed by WBFs (e.g. Chung, 2015). The WBF assured us that the majority of its risky suppliers are located in China, a fact which also pointed to high levels of potential barriers.…”
Section: Methodsmentioning
confidence: 99%